Bayu Wetan As An Inspiration For The Percussion Of The Hips Creations | Bayu Wetan Sebagai Inspirasi Tabuh Kreasi Pepanggulan - Dwi Antara Putra; Ni Ketut Dewi Yulianti (GHURNITA: Jurnal Seni Karawitan, 2022)
This work is poured into the composition of the Tabuh Kreasi Pepanggulan. The analogy is with the expression of the stylist's feelings through the natural phenomenon of the east wind blowing. This idea arose when the stylist was sitting in one of the seats in the stylist's own house, and the stylist felt a gust of wind coming from the east that blew neatly and brought an atmosphere of beauty, the coolness of the wind's strength, the stylist felt how the atmosphere was in the morning. Based on this phenomenon, the stylists got the inspiration to realize the beauty, coolness, and strength of the east wind that had approached the stylist's soul into a form of Pepanggulan's Creative Tabuh composition which was packaged using the Tri Angga structure, namely Kawitan, Pengawak, and Pengcet. Bayu and wetan are two words that have different meanings, but the stylist will make these meanings into one complete work. The word "bayu" in Sanskrit means wind, and the word "wetan" means east, apparently white, the script is "dang" with the magic of Sang Sadyoja (Bandem, 1986). So "bayu wetan" can be interpreted as a philosophical concept from Dewa Iswara who controls the east direction and controls the direction of the wind in the east.